PENINGKATAN KEMAMPUAN KOGNITIF ANAK MELALUI KEGIATAN MOTORIK KASAR PADA ANAK USIA DINI: IMPROVEMENT OF CHILDREN'S COGNITIVE ABILITIES THROUGH GROSS MOTOR ACTIVITIES IN EARLY CHILDHOOD - Agustin, Asty; Zahra, Firza Hardyn Aira; Munawaroh, Hidayatul (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2023)
This article reviews improving cognitive abilities through gross motor skills in early childhood in learning to walk, practicing balance and running. This article aims to describe, train and find the impact of implementing children's learning to walk, train balance so they can run in the gross motoric process of early childhood.This type of article is a descriptive article with a naturalistic paradigm. The study instruments are observation and key instruments in research. The sources for this study are the results of interviews with primary school teachers and several books, articles and journals about cognitive and gross motoric development in early childhood. Jean Piaget's theory of cognitive development or Piaget's theory states that intelligence changes as children grow, not only about acquiring knowledge, children must also develop or build their mentality. Then, children learn on their own without influence from parents or older children. Children are motivated to learn by themselves and do not need prizes as motivation. In other words, the way to improve a child's cognitive abilities is by giving him lots of experiences through stimulation.This article reviews improving cognitive abilities through gross motor skills in early childhood in learning to walk, practicing balance and running. This article aims to describe, train and find the impact of implementing children's learning to walk, train balance so they can run in the gross motoric process of early childhood.This type of article is a descriptive article with a naturalistic paradigm. The study instruments are observation and key instruments in research. The sources for this study are the results of interviews with primary school teachers and several books, articles and journals about cognitive and gross motoric development in early childhood. Jean Piaget's theory of cognitive development or Piaget's theory states that intelligence changes as children grow, not only about acquiring knowledge, children must also develop or build their mentality. Then, children learn on their own without influence from parents or older children. Children are motivated to learn by themselves and do not need prizes as motivation. In other words, the way to improve a child's cognitive abilities is by giving him lots of experiences through stimulation.